2013
DOI: 10.1128/jb.00505-13
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Host Hemoglobin Binding by the Staphylococcus aureus Clp Proteolytic System

Abstract: Protein turnover is a key process for bacterial survival mediated by intracellular proteases. Proteolytic degradation reduces the levels of unfolded and misfolded peptides that accumulate in the cell during stress conditions. Three intracellular proteases, ClpP, HslV, and FtsH, have been identified in the Gram-positive bacterium Staphylococcus aureus, a pathogen responsible for significant morbidity and mortality worldwide. Consistent with their crucial role in protein turnover, ClpP, HslV, and FtsH affect a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 77 publications
3
43
0
Order By: Relevance
“…The underlying mechanism remains unclear but will be the subject of further studies. The in vivo selection of a mutation that abolished the synthesis of the ClpX chaperone was surprising, as ClpX is required for the virulence of S. aureus in animal models of infection (22,23). The severely decreased virulence of the clpX mutant has been attributed to the reduced expression of a number of major virulence factors, including hemolysins and protein A (22,24,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying mechanism remains unclear but will be the subject of further studies. The in vivo selection of a mutation that abolished the synthesis of the ClpX chaperone was surprising, as ClpX is required for the virulence of S. aureus in animal models of infection (22,23). The severely decreased virulence of the clpX mutant has been attributed to the reduced expression of a number of major virulence factors, including hemolysins and protein A (22,24,25).…”
Section: Discussionmentioning
confidence: 99%
“…The highly conserved ClpX chaperone has a dual role in the cell; it targets proteins for degradation by associating with the ClpP peptidase, and, independently of ClpP, it facilitates protein folding and interactions (21). Interestingly, inactivation of clpX severely reduced the virulence of S. aureus in both localized and systemic models of infection, suggesting that ClpX is indispensable for S. aureus during infection (22,23). Consistent with this finding, the clpX mutant expresses substantially reduced amounts of important virulence factors, such as hemolysins and protein A (22,24,25).…”
mentioning
confidence: 99%
“…Tryptic soy broth (TSB) (Difco) was used as an iron-rich medium. Iron-restricted media were generated by adding the iron chelator 2,2-dipyridyl (DIP) (31). In short, overnight cultures of S. lugdunensis strains were subcultured (1:100) into TSB alone or with 350 M DIP.…”
Section: Methodsmentioning
confidence: 99%
“…In various pathogenic microorganisms, such as Listeria monocytogenes, Streptococcus pneumoniae and S. aureus, ClpP proteases have been identiied in in vivo expression studies as an important virulence factor [44,48,49]. Knockout studies of the clpP ATP-dependent gene in S. aureus, followed by global transcriptional analysis using DNA microarray technology, showed that the loss of clpP leads to complete derepression of transcription of the CtsR gene (or yacG, a polypeptide transcriptional regulator).…”
Section: Mechanisms For Vancomycin Resistance Associated To Modiicatimentioning
confidence: 99%
“…ClpP plays an essential role in the degradation of pathogen cell wall but also in the regulation of their virulence [44]. The ClpP components in S. aureus are responsible for initiating physiological adaptive responses against diferent external pressures, including extreme changes in temperature, osmolarity and oxidative stress [45].…”
Section: Mechanisms For Vancomycin Resistance Associated To Modiicatimentioning
confidence: 99%